ANALISIS PERBANDINGAN PERFORMA QOS, PPTP, L2TP, SSTP DAN IPSEC PADA JARINGAN VPN MENGGUNAKAN MIKROTIK - Wa Ode Zamalia; LM. Fid Aksara; Muh. Yamin (Informatics Engineering Department of Halu Oleo University, 2018)
Tunnel PPTP, L2TP, SSTP, and IPsec are VPN types that have been widely supported by network protocols to apply to many computer network devices. These four methods are applied alternately on Mikrotik. In each applied method, will be analyzed using Wireshark application, with Quality of Service (QoS) parameters consisting of Packet Loss, Delay, and Throughput. Tests performed on four clients which connected to the access point. Testing is done with two kinds of networks, the first one in which all client access web for download purpose and the second one in which all client access web for streaming video. The security testing result between PPTP tunnels, L2TP, SSTP, and IPSec shows that security level built by IPsec tunnels better than the L2TP, SSTP, and PPTP tunnels. Moreover, based on the results of testing on performance, security and test findings obtained that IPsec VPN tunnel better than tunnel VPN PPTP L2TP and SSTP.Keywords— Layer 2 Tunneling Protocol, Point to Point Tunneling Protocol, Quality of Service (QoS), Secure Socket Tunneling Protocol, Virtual Private Network DOI: 10.5281/zenodo.1444898